Upaya Pembinaan Fatayat Nahdlatul Ulama (NU) Dalam Pembentukan Karakter Religius Terhadap Perempuan di Desa Mlipak - Tasmara Shahnas; Ngarifin Shidiq; Muhammad Saefullah (STIKes Ibnu Sina Ajibarang, 2024)
The formation of religious character is not formation based on memorization and verbal knowledge. Religious character formation is the formation of religious behavior through habitual action and emulating educators, parents, leaders and society which is the broad environment for developing one's character. The research objectives are: 1) to determine the efforts of Fatayat NU to develop the religious character of women in Mlipak Village; 2) to find out what material is presented for the guidance of Fatayat NU in the formation of religious character for women in Mlipak Village; 3) to determine the supporting and inhibiting factors in the implementation of Fatayat NU coaching in the formation of religious character for women in Mlipak Village. More than just religious knowledge, the formation of religious character is an ongoing process that involves action and example. It is hoped that this research can provide a deeper understanding of the role of Fatayat NU in instilling religious values in women in Mlipak Village, as well as identifying factors that support and hinder the implementation of religious character development. This thesis uses a qualitative research approach with descriptive research type. Researchers will collect data through three methods, namely interviews, documentation and observation. The research subjects consisted of the Chair of Fatayat NU, members of Fatayat NU, and young women in Mlipak Village. This research reveals various interesting findings regarding Fatayat NU's efforts to instill religious values in women in Mlipak Village, Wonosobo. Fatayat NU plays an important role in instilling religious values in women in Mlipak Village through various coaching activities and materials presented. Even though there are several inhibiting factors, support from various parties is the key to the success of Fatayat NU's efforts to create religious women in Mlipak Village.